THE INFLUENCE OF URBANIZATION TO THE WATER INFILTRATION ZONE ON BANYUMANIK SUB-DISTRICT, SEMARANG CITY, CENTRAL JAVA, INDONESIA - Budianta, Wawan; Firmansyah, Wahyu; Setijadji, Lucas Donny (Institut Teknologi Nasional Yogyakarta, 2024)
The high growth of developed land in the Banyumanik Sub-District, especially in residential and commercial areas, occurred due to the high demand for housing, lifestyle fulfillment, and speculation and investment by the upper-middle-class society. The reduction or loss of land with vegetation cover in the Banyumanik Sub-District increases the potential for flooding due to more significant surface runoff than water absorption during heavy rainfall. This research used integrated spatial analysis to generate information on the critical level of water infiltration in the research area using the Analytical Hierarchy Process (AHP) method. Both primary and secondary data collected will be compiled and subjected to spatial analysis to address the issues at hand. The weight of each parameter class produced by the AHP method is used for modeling and includes infiltration rate, land use, slope, and lithology parameters. The criticality level of the water infiltration zone in the southern part of Banyumanik Sub-District indicates that the water infiltration condition in the research area consists of good class at 13.589%, naturally normal at 18.405%, started to be critical at 16.114%, slightly critical at 20.764%, critical at 18.286%, and very critical at 12.841%. Changes in land use in the research area have become the primary factors causing alterations in the water infiltration conditions. Infiltration wells are one of the solutions to mitigate runoff as part of sustainable rainwater management. The government plays a crucial role as a policymaker in making decisions to address issues related to urban area development towards sustainable development.